Proses Perencanaan TTI (trade,tourism,investment) Forum dalam Event Trade Expo Indonesia 2018 - Vanya Fajria; Dewi Winarni Susyanti (Bisnis Event, 2021)
Trade Expo Indonesia is a B2B international trade exhibition (Business to business) designed to increase the growth of export and export markets. The 2018 Trade Expo Indonesia (TEI) exhibition is an exhibition held by the Directorate General for National Export Development (DGNED) - Ministry of Trade of the Republic of Indonesia. Organized by PT. Debindomulti Adhiswasti on October 23-28 2018 at ICE BSD Tangerang, this exhibition was the 33rd international trade exhibition. This exhibition displays various products from Indonesia. Over the past few years, Indonesia has achieved positive growth trends in various products and globally, which must be and more important, because Indonesia is also competing with other countries in global opportunities. To continue to improve export performance, the government has been proactively inviting and investors for direct agreements with export product and service providers of the Indonesia Trade Expo Indonesia (TEI). Along with the Trade Expo Indonesia (TEI) 2018 exhibition, Trade Expo Indonesia (TEI) 2018 also presents parallel activities named TTI (trade, tourism, investment) Forum which is a forum for exporters, prospective exporters, investors, potential investors, business world and government officials meet and learn information and solutions about issues in discussions and opportunities from various parties involved from the related sector. There is a TTI Forum several things that must be done during the planning period of the TTI Forum implementation. The research was conducted with the results of interviews, and was active with live programs, both in planning, implementation and post event.